PENGARUH PENGGUNAAN TEKNOLOGI PEMBELAJARAN TERHADAP KEMAMPUAN MERANCANG RPP MAHASISWA PGSD - Dinda Fajar Chairani; Gracie Angelica; Jesi Alexander Alim; Mitha Dwi Anggriani (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to analyze the effect of using educational technology on the ability of elementary teacher education (PGSD) students to design lesson plans (RPP). The research employed a quantitative method with a pretest–posttest control group design. The sample consisted of 30 fifth-semester PGSD students selected through purposive sampling. The experimental group was given treatment by using educational technologies (Canva, Google Classroom, Kahoot) in preparing lesson plans, while the control group designed RPP conventionally. The research instruments included a test of lesson plan design skills administered at pretest and posttest, and a Likert-scale questionnaire to support data on student perceptions. Results indicated that the experimental group’s ability increased from medium (M = 70.12) to high (M = 82.35), while the control group only improved slightly (M = 69.85 to M = 72.10). A t-test showed a significant difference between groups (t = 3.52; p < 0.05). It is concluded that integrating educational technology positively affects PGSD students’ ability to design RPP, enhancing creativity and readiness as future teachers in the digital era.